Corporate income tax: Experiences of implementation in the Republic of Serbia - Božić-Miljković Ivana M. (Megatrend Revija)
Companies are independent economic entities that have the competence and legitimacy to carry out a certain type of activity. As such, companies act in the market, are in the role of buyers and sellers, enter into contracts, own property, incur debts and resolve potential problems in legal disputes. Just like any other person who engages an activity and earns income from it, the company must pay taxes on the profit it earns from this activity. Profit tax belongs to the category of direct taxes. Revenue from corporate income tax accounts for approximately 6% of the total tax revenue of the Republic of Serbia. The rights and obligations of companies as taxpayers under this measure of tax policy in the Republic of Serbia are regulated by the Law on Profit Tax of Legal Entities. The importance of profit tax as a measure of tax policy can be observed and analyzed from the aspect of its impact on state revenues. In this context, the corporate income tax is one of the elements of achieving the basic fiscal goal: collecting public revenues to cover public expenditures. Also, the application of regulations in the field of taxation of positive business results has certain implications for the company's operations, and as such, is very important for business decision-makers in the company. That part of the fiscal policy determines the total volume of investments in equipment and facilities, the types of those investments and the method of their financing. The effects of the application of legal provisions, which in practice regulate the issue of profit tax, on domestic companies are often compared with the effects that this measure of fiscal policy has on companies and states from the region. On the other hand, the experiences of the European Union in this area are of great importance, and the monitoring of those experiences, as well as the application of European regulations in this area, can be extremely useful from the perspective of the state and its economic entities.